Membranous nephropathy: A diagnostic and therapeutic challenge? - Gameiro,Joana (2017)
Membranous nephropathy (MN) is the most common cause of nephrotic syndrome in Caucasian adults aged over 60 years old. Approximately two thirds of cases of membranous nephropathy (MN) in adults are primary (idiopathic), and the remaining are secondary forms which have been attributed to a variety of agents or conditions. Recent advances in pathophysiology and the availability of new laboratory diagnostic methods reinforce the importance of differentiating idiopathic from secondary MN, given the repercussions on therapy. We present the case of a 71-year-old Caucasian male referred to Nephrology due to nephrotic syndrome. He had a history of gastric adenocarcinoma and of parathyroid cancer, but was considered cured. Investigation excluded immunologic disease, dysproteinaemia, chronic infection and active malignancy. Kidney biopsy was performed and confirmed MN. Histological characterization of IgG subtypes was not available, nor was biopsy study for the reactivity for PLA2 receptor. The patient was started on conservative treatment, but, after a one-year follow-up, presented persistent nephrotic proteinuria (5g/day) and renal function decline (serum creatinine of 1.6mg/dL). Serological determination of phospholipase A2 receptor antibody was positive, but with borderline titer. Considering his history of malignancy as well as kidney function deterioration, Rituximab was prescribed. At one year of follow-up the patient has proteinuria of 500 mg/day, stable renal function (serum creatinine of 1.2 mg/dL) and negative serum anti-PLA2 receptor antibody. Despite the recent availability of serological determination of phospholipase A2 receptor antibody and histological characterization of IgG subtypes, in this case they did not allow us to safely distinguish between idiopathic and secondary MN. Therefore the past medical history played a significant part in the therapeutic option. Recent studies suggest that Rituximab has similar results to non-specific immunosuppression, promoting remission in patients with severe and persistent MN, with less adverse effects, and thus can be considered as first-line therapy